STATIC AND DYNAMIC ANALYSIS OF SHALYSAND RESERVOIR CHARACTERIZATION IN BEKASAP FORMATION FOR FIELD DEVELOPMENT AT PUNGUT OIL FIELD - Raya Barkah , Rd.Rai
Pungut field in Central Sumatra Basin has produced 64.8 MMBO since October 1957 the majority of which has come from Lower Miocene age of Bekasap and Bangko Formation reservoirs. To date, there were 39 wells have been drilled. The depletion of average reservoir pressure close to bubble point caused the decreasing of oil production in this structure. Therefore, a waterflood project then applied to moving remaining reserves since January 2005. This research was performed in an attempt to gain a better understanding on shalysand reservoir characteristic of Bekasap Formation in Pungut Oil Field, Central Sumatera Basin. Based on several wells data in this field reveals a variation of reservoir characteristic, specially heterogeneity and facies distribution, which affected the quality of reservoir. In order to solve this problem, an integrated static and dynamic study was carried out, which include core description, stratigraphic analysis, seismic attribute analysis, geometry and property mapping and production data. The lithological study was end up with an identification of five facies association named Tidal Channel, Tidal Sand Flat, Mud Flat and Tidal Sand Bar which were interpreted as Estuarine deposition environment. Generally, these B and C reservoir were deposited in a Transgressive condition (Transgressive System Tract). The studied of both reservoir B and C concluded that reservoir B has a better quality reservoir compare to reservoir B in term of porosity and permeability. The differences exhibit a reservoir heterogeneity, which were controlled by facies and its depositional environment. Validation of dynamic data was also confirmed this analysis. By having a better understanding on reservoir B and C characteristics, a proper methods/application can be applied to optimize oil production as part of a plan for further development (POFD).